How risky is the German pension system? The volatility of the internal rates of return - Matthias Heidler; Bernd Raffelhüschen (Albert-Ludwigs-Universität Freiburg, Forschungszentrum Generationenverträge (FZG), 2005)
In this paper we analyze exemplarily the volatility of the internal rates of return of the German pension system over the life-cycle of an individual born in 1957. The outcome is compared to an alternative defined-contribution or defined-benefit policy. Based on the actual data, our results show the volatility of the internal rate of return to be significantly higher under the actual policy. We furthermore find that the sustainable internal rates of return are close to zero for the youngest male cohorts and positive for females for optimistic growth scenarios. In more realistic scenarios things turn worse.
Keywords: H55; J18; 330; Risk; internal rate of return; sustainability